Systematic imagery training for Taijiquan competitive routines: A case study - Ning Su; Gangyan Si; Wei Liang (Asian Journal of Sport and Exercise Psychology)
Using a case study format, this investigation examines the effectiveness of a systematic imagery training program on the timing accuracy and movement stability in Taijiquan competitive routines performed by a 31-year-old female member of the Hong Kong Wushu team, who is a Wushu World Champion. The training program was conducted under close supervision over a period of 11 weeks, with the imagery training sessions covering five components: imagery content, imagery perspective, imagery speed, imagery background, and placement of distractors. Measures of psychological variables (i.e., imagery abilities and self-confidence) and also physical practice (i.e., actual performance) were implemented pre-, during, and post-intervention, so that the effectiveness of the intervention could be evaluated. Results showed that the systematic imagery training not only helped the development of imagery ability and the building of self-confidence, but also contributed to the athlete's excellent performance in a target competition. The findings suggest that the imagery training intervention positively impacted timing accuracy and stable execution of movements during actual performances.